RF38 'I've always done what I was told by the medical people' – a mixed methods study of older people's reasons for attendance at a new fall prevention clinic. (September 2018) - McHugh, S; Racine, E; Cronin, F; O'Sullivan, L; Moriarty, E; Turvey, S; Barry, P; O'Connor, K; Timmons, S; Kearney, PM
Abstract : Background: Falls are one of the most serious and common threats facing older adults. Multifactorial falls risk assessment can reduce the rate of falls among community dwelling older adults and is recommended as a first step in the early detection and management of risk factors. It is used as a gateway for older people to access evidence-based interventions targeting their individual risk factors. However, effective interventions will only reduce the rate and risk of falls if there is a high level of uptake in the population and suboptimal uptake is a common challenge. The aim of this study is to understand the reasons for the patterns of uptake of multifactorial fall risk assessment clinics in the community. Methods: A convergent mixed methods study design was used. Data on attendance/non-attendance during the first 12 months at each clinic (n=4) were extracted from a centralised administrative database. Semi-structured interviews (n-16) were conducted with a purposive sample of people who attended a clinic (criteria: male/female, age: 55–69, 70–79, 80+, and clinic), selected from those who had opted in during a preceding service-user experience survey. Administrative data were analysed descriptively using STATA (v13) software. Thematic analysis was performed and themes were mapped onto the Theoretical Domains Framework (TDF). Data were merged during analysis and interpretation using qualitative themes to expand on the patterns emerging in the quantitative data. Results: Of the 588 older adults invited, 484 attended the assessment which resulted in an uptake rate of 82.3% (range: 77.5–86.1). Reasons for attending were summarised into themes which mapped onto 10 theoretical domains. Key themes identified were always attending medical appointments and adhering to medical advice (social/professional role and identity), having a positive attitude towards health services (optimism), being linked in with health professionals and community services (environmental context and resources) and having strong social support from family and friends (social influences). Other themes included understanding what the clinic was about (knowledge), having a fear of falling (emotion), supposing the benefits of attending (beliefs about consequences) and wanting to prevent further falls (goals). Conclusion: The results suggest older people attend fall prevention services if they have existing (positive) links to health services and are well supported in their homes and communities. To improve the spread of fall prevention programmes, there is a need to reach older adults who are less well supported.